Theoretical Review on Prediction of Motion Response using Diffraction Potential and Morison - Siow, C.L.; Koto, J.; Yasukawa, H.; Matsuda, A.; Terada, D.; Guedes Soares, C. (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2015)
This paper reviewed the capability of the proposed diffraction potential theory with Morison Drag term to predict the Round Shape FPSO heave motion response. From both the self-developed programming code and ANSYS AQWA software, it can be observed that the diffraction potential theory is over predicting the Round Shape FPSO heave motion response when the motion is dominated by damping. In this study, Morison equation drag correction method is applied to adjust the motion response predicted by diffraction potential theory. This paper briefly present the procedure to integrate the Morison equation drag term correction method with the diffraction potential theory and then, the proposed numerical method was applied to simulate the Round Shape FPSO heave motion response. From the comparison, it can be concluded that Morison equation drag correction method is able to estimate the FPSO heave response in the damping dominated region and provides more reasonable motion tendency compare to the diffraction potential theory without consider the drag effect in the calculation.